La cárcel en Colombia : espacio para la venganza y la reincidencia - Ossa López, María Fernanda, (CONtexto (Medellín, Colombia), 2016)
Analyzes recidivism in Colombia on the basis of a survey of 102 female inmates of the Centro Carcelario y Penitenciario El Pedregal of Medellín, Colombia. The study reflects the current situation of prisons and the difficult socio-economic and cultural conditions that lead people to seek out crime as a solution.